IMPLEMENTASI METODE MUHAWARAH UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM PEMBELAJARAN BAHASA ARAB: IMPLEMENTATION OF MUHAWARAH METHOD TO IMPROVE STUDENT SKILL IN ARABIC LEARNING - Naila; Syafii (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
This research is a study that discusses 1) How the application of the muhawarah method can be effective in learning Arabic, 2) The advantages and disadvantages of the muhawarah method. The muhawarah method is a conversational exercise using Arabic which is carried out by students every day. This method is usually required to be applied in every language cottage to speak Arabic. This method is not only based on the maharah kalam. However, it has an impact on the aspects of maharah qira'ah, maharah istima', and maharah kitabah. So this method not only facilitates the speaking, but has an impact on other aspects. The purpose of this research is to find out whether using this muhawarah method has a very good impact on students. In this research, the muhawarah method uses a descriptive research method where, this study describes the description of the events that occurred.